Analisis Kemampuan Literasi Siswa Terhadap Keterampilan Membaca Dongeng dalam Pemanfaatan Aplikasi Let’s Read - S, Listiani; Ezmar, Ezmar; Agustisa, Mutia (Universitas Negeri Padang, 2025)
This study aims to analyze students' literacy skills in reading fairy tales through the use of the digital application Let's Read for seventh-grade students at SMP Negeri 1 Peusangan Selatan. The background of this research is the low literacy ability of students who still rely on conventional teaching methods and have limited access to interactive digital reading materials. This study employs a qualitative descriptive research approach with data collection techniques including observation, documentation, and interviews. The results show that before using the Let's Read digital application, most students had difficulty understanding the content of fairy tales and lacked motivation to read. After utilizing the Let's Read application, there was a positive improvement in students' fairy tale reading abilities in terms of content comprehension, reading interest, and learning motivation. The Let's Read digital application proved effective in providing engaging, easily accessible reading materials aligned with the characteristics of the digital generation. Therefore, the use of digital applications like Let's Read can be a solution to improve students' reading literacy, especially in fairy tale texts, as well as promote the development of critical and creative thinking skills in the current digital era.Keywords: Literasi, membaca dongeng, Let's Read, pembelajaran digital, siswa SMP.